Exploration by molecular networking of Strychnos alkaloids reveals the unexpected occurrence of strychnine in seven Strychnos species. (August 2022) - Bonnet, Olivier; Beniddir, Mehdi A.; Champy, Pierre; Kagisha, Védaste; Nyirimigabo, Alain; Hamann, Carla; Jgerenaia, Giorgi; Ledoux, Allison; Tchinda, Alembert Tiabou; Angenot, Luc; Frédérich, Michel
Abstract: Introduction: Plants of the Strychnos genus, which include about 200 species, are used for multiple traditional purposes as hunting poison, for example, and have shown interesting pharmacological properties, especially curarizing and tetanizing, but also against malaria. Many monoterpene indole alkaloids have already been isolated and identified. Among them, there is strychnine, a famous alkaloid that can cause death by asphyxiation. Objective: Investigate alkaloidic molecular diversity from Strychnos genus using molecular networking technique and study the Strychnos genus from a chemotaxonomic point of view. Material and methods: Twenty-eight different species and different plant parts were ground into powder using a grinder. The methanolic extracts were carried out using a pressurized solvent extraction and the alkaloid extract was performed manually with a separating funnel. The extracts were analyzed by HPLC-ESI(+)-Q/TOF. The data were processed using MZmine 2 software and the molecular network was generated on the GNPS platform. The study of the generated molecular network allowed the detection of various alkaloids. Among these is the famous strychnine which has been detected in 7 new Strychnos species not yet described as strychnine producers. This identification was investigated using orthogonal approaches, namely TLC, NMR, HPLC-UV and UHPLC-ESI(+)-Q/TOF analyses. The LOD by HPLC-UV of strychnine was also determined. Results: Further analyses allowed to confirm the presence of strychnine in S. densiflora trunk barks but also to show the presence of strychnine with high probability in the trunk barks of S. camptoneura, S. congolana, S. boonei, and S. tchibangensis, and in the leaves of S. usambarensis . About the trunk barks of S. tricalyisoides, the probability of a strychnine content remains low. Conclusion: This work exemplified the efficiency of molecular networking in identifying known metabolites (major and minor alkaloids) involved in the chemotaxonomic study of plants from Strychnos genus. Graphical abstract: Image 1 Highlights: The pantropical plants of Strychnos genus contain biologically active monoterpene indole alkaloids. The Leeuwenberg's classification of Strychnos into 12 sections is questioned. 44 crude extracts from 27 Strychnos species were studied by HPLC-ESI(+)-Q/TOF and by molecular networking analysis. Strychnine was identified in 3 well-known and 1 new species, and detected in 5 additional species by HPLC-MS/MS analysis. This study is a contribution to the chemotaxonomic understanding of the species belonging to Strychnos genus.